Gender impacts the post-exercise substrate and endocrine response in trained runners - Martin William F; Pikosky Matthew A; Gaine P Courtney; Vislocky Lisa M; Rodriguez Nancy R (Taylor & Francis Group, 2008)
Abstract Background Although several studies have investigated gender differences in the substrate and endocrine responses during and following endurance exercise, few have studied sex differences during a more prolonged recovery period post endurance exercise. The purpose of this study was to compare and characterize the endocrine and substrate profiles of trained male and female adult runners during the three-and-a-half hour recovery period from an endurance run. Methods After consuming a euenergetic diet (1.8 g·kg-1·d-1 protein, 26% fat, 58% carbohydrates, 42.8 ± 1.2 kcal/kg body weight) for 8 days, blood was collected from trained male (n = 6, 21 yrs, 70 kg, 180 cm, 9% body fat, VO2peak 78.0 ± 3.4 mL·kg FFM-1·min-1) and female (n = 6, 23 y, 66 kg, 170 cm, 29% body fat, VO2peak 71.6 ± 4.5 mL·kg FFM-1·min-1) endurance runners at rest and during recovery from a 75 min run at 70% VO2peak. Circulating levels of glucose, lactate, free fatty acids (FFAs), insulin, cortisol, growth hormone (GH), and free insulin-like growth factor I (IGF-I) were measured. Results During the recovery period, females experienced increases in glucose, lactate and insulin while no changes were noted in men (P < 0.05). Males experienced increases in GH and decreases in IGF-I levels respectively (P < 0.05) while no changes were observed in females. FFA levels increased during recovery from endurance exercise, but changes were not different between genders. Conclusion These data further document gender differences in substrate and endocrine changes during a prolonged recovery period following endurance exercise. Future studies are needed to evaluate the effect of differing diets and nutritional supplements on these gender-specific post-exercise substrate and endocrine differences.